THE PRODUCTION AND MARKETING OF CARP ( Cyprinus carpio ) CONSUMPTION IN SUBS-DISTRICT RAO SELATAN DISTRICT PASAMAN THE PROVINCE OF WEST SUMATRA - Bathara, Lamun; ', Sukron; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aims to analyse the production of , productivity cultivator of the carp, the cost and profit by each institution the marketing of carp in the subs-district Rao Selatan District Pasaman the Province of West Sumatra.Based on the results of research , cultivator of the pool with a broad 3,500 m2 an average of producing 4.461,25 kg per harvest , productivity 1.27 kg per square and the cost of Rp 70.672.000 with profit of Rp 9.630.500 / harvest .Cultivator of the pool with a broad 5,000 m2 producing 6.240 kg per harvest , productivity 1.27 kg per square and the cost of Rp 103.972.000 with profit of Rp 8.848.000 / harvest . With broad cultivator of the m2 kolam7.500 as many as 8.532,5 kg per harvest , productivity 1,14 kg per square and the cost of Rp 143.372.000 with profit of Rp 10.213.000 / harvest .Intermediary traders 1 issue the average cost as much as Rp 149.330.000 to the advantage Rp 15.420.000 per month .Intermediary traders 2 issued the average cost as much as Rp 120.830.000 to the advantage Rp 13.170.000 per month .Intermediary traders 3 spend money an average of Rp 107.250.000 to the advantage Rp 10.020.000 per month .While traders a retailer issued the average cost as much as Rp 8.552.000 to the advantage Rp 1.447.000 per month.Key words: production, productivity, cost, profit